2018
DOI: 10.1002/jbio.201800062
|View full text |Cite
|
Sign up to set email alerts
|

Simple 3‐criteria‐based ex vivo confocal diagnosis of basal cell carcinoma

Abstract: Ex vivo CM allowed intraoperative examination of BCC based on only 3-criteria with high sensitivity and specificity, provided useful information on tumor subtype and showed that both experienced and non-experienced examiners may use this diagnostic approach with excellent results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
(56 reference statements)
1
21
0
2
Order By: Relevance
“…In the current study, acridine orange was selected because it has been proven to only stain DNA, providing a strong contrast between nuclear morphology and the surrounding background, without altering tissue morphology . To date, ex vivo FCM has been evaluated for its correlation with the histopathology in healthy skin, its application in diagnosis of basal cell carcinoma, squamous cell carcinoma, rare malignant adnexal tumors, such as the eccrine syringomatous carcinoma, and conjunctival lesion evaluation in ophthalmology, for assessment of tumor margins on fresh tissue excisions in Mohs surgery. Other application was the differential diagnosis of melanocytic lesions from healthy skin .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, acridine orange was selected because it has been proven to only stain DNA, providing a strong contrast between nuclear morphology and the surrounding background, without altering tissue morphology . To date, ex vivo FCM has been evaluated for its correlation with the histopathology in healthy skin, its application in diagnosis of basal cell carcinoma, squamous cell carcinoma, rare malignant adnexal tumors, such as the eccrine syringomatous carcinoma, and conjunctival lesion evaluation in ophthalmology, for assessment of tumor margins on fresh tissue excisions in Mohs surgery. Other application was the differential diagnosis of melanocytic lesions from healthy skin .…”
Section: Discussionmentioning
confidence: 99%
“…1) ist die weltweit am häufigsten auftretende Form vom Hautkrebs und ist die bestuntersuchte dermatologische Entität in der Geschichte der ex vivo KLM, inklusive Studien zum ex vivo KLM-Einsatz in der Mohs-Chirurgie [4, 5, 8, 20 -22]. In einer der kürzlich publizierten Arbeiten zur ex vivo KLM-Untersuchung des BZK konnte gezeigt werden, dass eine schnelle und einfache mikroskopische Beurteilung des BZK in der ex vivo KLM sogar nur anhand einer vereinfachten 3-Kriterien-basierten Tumorevaluation möglich ist und dass es die diagnostischen und therapeutischen Verfahren in der Dermatologie einschließlich der mikroskopisch kontrollierten Chirurgie beschleunigen kann [5]. Die ex vivo KLM ermöglichte die intraoperative Untersuchung von BZK mit hoher Sensitivität und Spezifität, lieferte nützliche Informationen zum Tumorsubtyp und zeigte, dass sowohl erfahrene als auch nicht erfahrene Untersucher diesen diagnostischen Ansatz mit hervorragenden Ergebnissen anwenden können [5].…”
Section: Basalzellkarzinomunclassified
“…In einer der kürzlich publizierten Arbeiten zur ex vivo KLM-Untersuchung des BZK konnte gezeigt werden, dass eine schnelle und einfache mikroskopische Beurteilung des BZK in der ex vivo KLM sogar nur anhand einer vereinfachten 3-Kriterien-basierten Tumorevaluation möglich ist und dass es die diagnostischen und therapeutischen Verfahren in der Dermatologie einschließlich der mikroskopisch kontrollierten Chirurgie beschleunigen kann [5]. Die ex vivo KLM ermöglichte die intraoperative Untersuchung von BZK mit hoher Sensitivität und Spezifität, lieferte nützliche Informationen zum Tumorsubtyp und zeigte, dass sowohl erfahrene als auch nicht erfahrene Untersucher diesen diagnostischen Ansatz mit hervorragenden Ergebnissen anwenden können [5]. Es wurde auch in einer aktuell veröffentlichten Arbeit mit ähnlichen Ergebnissen bestätigt, dass die ex vivo KLM ein neues vielversprechendes Instrument in der dermatologischen Diagnostik darstellt, welche sich als eine schnellere Alternative zur Gefrierhistologie beim BZK anbietet und eine Sensitivität von 79,8 % sowie eine Spezifität von 95,8 % zeigt [20].…”
Section: Basalzellkarzinomunclassified
“…So far, ex vivo CLSM has been mainly used in the intra‐ and postoperative assessment of skin tumours, the control of surgical skin margins and as an assistive method for Mohs microscopic surgery . A few studies have reported that ex vivo CLSM examination on freshly excised samples may also be helpful in the rapid diagnosis of inflammatory and infectious skin lesions .…”
Section: Introductionmentioning
confidence: 99%
“…2 So far, ex vivo CLSM has been mainly used in the intra-and postoperative assessment of skin tumours, the control of surgical skin margins and as an assistive method for Mohs microscopic surgery. [2][3][4][5][6][7][8][9][10] A few studies have reported that ex vivo CLSM examination on freshly excised samples may also be helpful in the rapid diagnosis of inflammatory and infectious skin lesions. [11][12][13][14][15] Recently, our group combined ex vivo CLSM examination with fluorescent-labelled antibody staining in the tissue sections of patients with melanoma, BCC 2 and cutaneous vasculitis, 16 and showed that ex vivo CLSM may have potential as an alternative method in immunofluorescent examination of skin.…”
Section: Introductionmentioning
confidence: 99%